Education, unemployment and migration - Eggert, Wolfgang; Krieger, Tim; Meier, Volker (Munich, 2007)
"This paper studies a two-region model in which unemployment, education decisions and interregional migration are endogenous. The poorer region exhibits both lower wages and higher unemployment rates, and migrants to the richer region are disproportionally skilled. The brain drain from the poor to the rich region is accompanied by stronger incentives to acquire skills even for immobile workers. Regional shocks tend to affect both regions in a symmetric fashion, and skilled-biased technological change reduces wages of the unskilled. Both education and migration decisions are distorted by a uniform unemployment compensation, which justifies a corrective subsidization."